PENERAPAN SISTEM PENGENDALIAN INTERN UNTUK MENGANTISIPASI PRAKTEK-PRAKTEK YANG TIDAK SEHAT DALAM TATA KELOLA KEUANGAN KOPERASI DI KABUPATEN GIANYAR - I D. N. Wiratmaja (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2010)
Social function inherent in the cooperative as a business entities and weak internal control is the trigger high levels of fraud in the cooperatives. Fraud carried out by unscrupulous managers is the main cause of the high level of bankruptcies in the cooperative. As the concern over the condition academic community of Udayana University through community service agency LPM organizes a lecture to introduce internal control for cooperation in Gianyar Regency. Lecturing was carried out on Saturday 27 September 2009 in Tampaksiring involving 56 participants from 19 cooperations throughout the Gianyar Regency. The evaluation result showed that the response of participants was positive and hoped that similar activities can be conducted on an ongoing basis. The main topics proposed by participants to the sustainability of the program is, training on the preparation of financial statements, training of computerized transaction processing, entrepreneurship and taxation.